Balanced Food Consumption Patterns in Elementary School Children: A Literature Review - Faradin, Anggia (Journal Nutrizione, 2025)
Balanced food consumption patterns are one of the important factors in supporting the growth and development of elementary school children. However, various studies show that school-age children still face challenges in implementing healthy eating patterns, which are influenced by low nutritional awareness, limited access to nutritious food, and the influence of the school and social environment. This study uses a qualitative approach with a literature study method that aims to examine various scientific findings related to factors that influence elementary school children's food consumption and effective intervention strategies. Data sources were collected from relevant national and international scientific journals in the last five to ten years. The results of the study show that low nutritional education in schools and families, as well as the dominance of unhealthy foods in school canteens, are the main causes of unbalanced consumption patterns. Educational and collaborative strategies are needed that involve the roles of schools, parents, government, and the community to shape children's healthy eating behavior in a sustainable manner. This study is expected to be a conceptual reference for designing nutrition education programs and healthy food policies in elementary education environments.